Exploring structure/property relationships to health and environmental hazards of polymeric polyisocyanate prepolymer substances—2. Dermal sensitization potential in the mouse local lymph node assay. (September 2022) - West, Robert J; Burleson, Stefanie; Gulledge, Travis; Miller, Jason W; Chappelle, Anne H; Krieger, Shannon; Graham, Cynthia; Snyder, Stephanie; Simon, Glenn; Plehiers, Patrick M
The sensitization potencies of twenty custom-designed monomer-depleted polymeric polyisocyanate prepolymer substances and their associated toluene diisocyanate (TDI), methylene diphenyl diisocyanate (MDI), hexamethylene diisocyanate (HDI), and isophorone diisocyanate (IPDI) monomer precursors were investigated by means of the mouse Local Lymph Node Assay (LLNA). These polymeric prepolymers were designed to represent the structural features and physical-chemical properties exhibited by a broad range of commercial polymeric polyisocyanate prepolymers that are produced from the reaction of aromatic and aliphatic diisocyanate monomers with aliphatic polyether and polyester polyols. The normalization of LLNA responses to the applied (15-45-135 mM) concentrations showed that the skin sensitization potency of polymeric polyisocyanate prepolymers is at least 300 times less than that of the diisocyanate monomers from which they are derived. The sensitization potency of the prepolymers was shown to be mainly governed by their hydrophobicity (as expressed by the calculated octanol-water partition coefficient, log Kow ) and surfactant properties. Neither hydrophilic (log Kow <0) nor very hydrophobic (log Kow >25) prepolymers stimulated lymphocyte proliferation beyond that of the dosing vehicle control. The findings of this investigation challenge the generally held assumption that all isocyanate (-N=C=O) bearing substances are potential skin (and respiratory) sensitizers. Further, these findings can guide the future development of isocyanate chemistries and associated polyurethane applications toward reduced exposure and health hazard potentials.